2015
DOI: 10.1007/s10534-015-9862-8
|View full text |Cite
|
Sign up to set email alerts
|

Mouse genetic background impacts both on iron and non-iron metals parameters and on their relationships

Abstract: Iron is reported to interact with other metals. In addition, it has been shown that genetic background may impact iron metabolism. Our objective was to characterize, in mice of three genetic backgrounds, the links between iron and several non-iron metals. Thirty normal mice (C57BL/6, Balb/c and DBA/2; n = 10 for each group), fed with the same diet, were studied. Quantification of iron, zinc, cobalt, copper, manganese, magnesium and rubidium was performed by ICP/MS in plasma, erythrocytes, liver and spleen. Tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 48 publications
3
22
0
Order By: Relevance
“…Aside from these immunological differences, BL6 and Balb/c mice also segregate from one another in their nutritional biochemistry, especially in regards to their iron management. We noted two previous studies from Cavey et al (Cavey et al., 2015) and Hahn et al (Hahn et al., 2009) that describe an intriguing association between iron homeostasis with the Th1/Th2 and M1/M2 bias of BL6 and Balb/c strains. Though both studies observed that Balb/c mice harbor more plasma and tissue iron than BL6 mice, they did not assess the underlying factors nor the expression of key iron regulatory genes that could explain the iron disparity in these mice.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…Aside from these immunological differences, BL6 and Balb/c mice also segregate from one another in their nutritional biochemistry, especially in regards to their iron management. We noted two previous studies from Cavey et al (Cavey et al., 2015) and Hahn et al (Hahn et al., 2009) that describe an intriguing association between iron homeostasis with the Th1/Th2 and M1/M2 bias of BL6 and Balb/c strains. Though both studies observed that Balb/c mice harbor more plasma and tissue iron than BL6 mice, they did not assess the underlying factors nor the expression of key iron regulatory genes that could explain the iron disparity in these mice.…”
Section: Discussionsupporting
confidence: 55%
“…Thus, we undertake this study to further explore whether the distinct iron levels in two widely used mouse models in biomedical research could be explained by the differences in the expression of major transporters/enzymes that maintain iron homeostasis. As previously reported (Cavey et al., 2015; Hahn et al., 2009), circulating and tissue iron levels of Balb/c mice were 2‐fold higher compared to BL6 mice; yet, the underlying factors contributing to their disparate iron status are not well‐elucidated. Consistent with their higher iron status, Balb/c mice displayed a higher iron absorption capacity on both apical ( Dcytb and DMT1 ) and basolateral ( Fpn and Heph ) compartments on duodenal epithelial cells.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…A core composition sufficient for the growth of P. gingivalis (MMBC-1) was further supplemented with components necessary for the growth of T. denticola and S. gordonii (MMBC-3). The quantification of iron in the MMBC media was performed by Inductively Coupled Plasma Mass Spectrometry (ICP-MS), on X-Series II from Thermo Scientific® equipped with collision cell technology (AEM2 Facility, University of Rennes 1), as previously described (Cavey et al, 2015). All three media contained less than 0.56 µM of iron (Table 1), making them suitable for iron metabolism/transport related studies.…”
Section: Tablementioning
confidence: 99%